Modelling Central Bank Behaviour in Nigeria: A Markov Switching Approach (2020)
The study models the behaviour of the Central Bank of Nigeria. An extended Taylor’s framework that accounted for exchange rate dynamics and political risk factors was adopted. In order to capture both ex ante and ex-post behaviours of the monetary authority in the country, Markov-Switching Dynamic Regression (MSDR) approach was employed. The period of investigation spanned 1981q1-2017q4. The study found that money supply in Nigeria was endogenous and showed, consequently, that the Central Bank of Nigeria (CBN) acted discretionally rather than stick to some monetary policy rules for the period under investigation. The results also suggested that political risk factors significantly moderated the behaviour of the CBN; especially during period of high-interest rate regime. With or without the effects of political risks being accounted for, low-interest rate regime was found to be more persistent than high-interest rate regime. With a relatively high persistence of low interest rate, the study found evidence for the popular Fisher’s effect and, then, suggested that inflation targeting should be one of the policy strategies of the monetary authority in Nigeria.